A review of effects of gender, age, and education on wage and productivity - Afrooz, Ahmad; Abdul Rahim, Khalid (EuroJournals Publishing, 2010)
This paper presents an overview of labour productivity and its relationship with wages. According to the classical and neoclassical economics, the equilibrium wage is determined by the intersection of supply and demand for labour. However, the labour market is shown as peculiar and different from other types of market. Several factors have been indicated to have effect on wages and productivity which have mostly been ignored. Among other, race, gender, age, education, training, firm size and ownership of firms are the important factors. In this research, empirical studies were categorized into three groups, namely gender and productivity, age and productivity, and education and productivity. These empirical studies showed that there was a positive relation between productivity and real wages. For instance, male and female workers and their age have different effects on wages and productivity. Similarly, the wage premium was found to increase with the years of schooling, and higher education was shown to yield higher productivity.